Sex-Specific Associations of Testosterone and Genetic Factors With Health Span - Zhao, Xiaoyu; Liang, Shuang; Wang, Nanxi; Hong, Tongtong; Sambou, Muhammed Lamin; Fan, Jingyi; Zhu, Meng; Wang, Cheng; Hang, Dong; Jiang, Yue; Dai, Juncheng (Frontiers in Endocrinology, 2021)
Background Previous studies have suggested associations between testosterone, genetic factors, and a series of complex diseases, but the associations with the lifespan phenotype, such as health span, remain unclear. Methods In this prospective cohort study, we analyzed 145,481 men and 147,733 women aged 38–73 years old from UK Biobank (UKB) to investigate the sex-specific associations of total testosterone (TT), free testosterone (FT), or polygenic risk score (PRS) with health span termination (HST) risk. At baseline, serum testosterone levels were measured. HST was defined by eight events strongly associated with longevity. PRS, an efficient tool combining the effect of common genetic variants to discriminate genetic risk of complex phenotypes, was constructed by 12 single-nucleotide polymorphisms related to health span from UKB (P ≤ 5.0 × 10−8). We used multivariable Cox regression models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results With a median follow-up time of 7.70 years, 26,748 (18.39%) men and 18,963 (12.84%) women had HST. TT was negatively associated with HST in men [HR per standard deviation (SD) increment of log-TT: 0.92, 95% CI: 0.88–0.97]. Inversely, both TT (HR per SD increment of log-TT: 1.05, 95% CI: 1.02–1.08) and FT (HR per SD increment of log-FT: 1.08, 95% CI: 1.05–1.11) presented an increased risk of HST in women. PRS was positively associated with HST risk (quintile 5 versus quintile 1, men, HR: 1.19, 95% CI: 1.15–1.24; women, HR: 1.21, 95% CI: 1.16–1.27). Moreover, men with high TT and low genetic risk showed the lowest HST risk (HR: 0.80, 95% CI: 0.73–0.88), whereas HST risk for women with both high TT and genetic risk increased obviously (HR: 1.32, 95% CI: 1.19–1.46). Similar joint effects were observed for FT in both genders. Conclusions We observed sex-specific associations that testosterone was negatively associated with HST risk in men and positively associated with HST risk in women. Genetic factors increased the HST risk, suggesting that participants with both high genetic risk and abnormal testosterone levels (high level in women or low level in men) should be the target for early intervention. Although our findings highlight the associations between testosterone and health span, further mechanistic studies and prospective trials are warranted to explore the causation behind.